DO MACROECONOMIC FACTORS AFFECT THE COMPOSITE STOCK PRICE INDEX? - Sianipar, Milka Rositi; Susilowati, Alicia Ulina; Tumangger, Ayu Bonita Sari; Silaban, Jenti Natalia; Hou, Amin; Rosita, Rosita (SULTANIST: Jurnal Manajemen dan Keuangan, 2024)
The movement of the stock market index is a barometer of economic growth, and can be used to make investment decisions. Many factors influence the movement of a stock index, particularly from the macroeconomic perspective. This study analyzes the effects of BI rate, exchange rate, and inflation on the Composite Stock Price Index (CSPI). This research is a quantitative descriptive study conducted on food and beverage companies listed on the Indonesia Stock Exchange (IDX) during the 2018-2022 period. Sixty companies were sampled and analyzed using multiple linear regression tests. Hypothesis testing uses the R2 (coefficient of determination) test, F, and t-tests. The results show that BI and exchange rates have a partially significant effect on CSPI. Inflation did not have a significant effect on the CSPI. However, simultaneous testing showed that the three variables affected the CSPI.